MODEL INTEGRASI TECHNOLOGY DALAM MEWUJUDKAN SUISTAINABLE ISLAMIC LEARNING DI INDONESIA - RAHMAYATI . (JURNAL ILMIAH MAKSITEK, 2019)
This study is entitled Technology Integration in Realizing Islamic Learning in Indonesia Model. The problem statement is the SWOT analysis of Islamic education on industry 4.0. The research objective is to examine the integration of Islamic education in the industrial era 4.0 so that it is functional. The research methodology is carried out in descriptive analysis from the literature. The conclusion is that the importance of technology for the existence and development of the world of Islamic education in the industrial era 4.0 where technology increases innovation, because it is real time for example using e book learning can be practically realized.